Influence of social media, print advertisement and event participation on product awareness of hausboom sparkling juice / Ahmad Danial Mohd Azlan, Khairool Ariffin Musa and Muhammad Hadzriz Mohd Yusoff - Mohd Azlan, Ahmad Danial; Musa, Khairool Ariffin; Mohd Yusoff, Muhammad Hadzriz (Arshad Ayub Graduate Business School, 2018)
Product awareness is important in establishing the existence of one’s product as consumers will associate the brand with the particular product that they aim to own. This study is focused on social media, print advertisements and event participation as the promotional strategies towards increasing the product awareness of Hausboom sparkling juice amongst the public. The area of Klang Valley is selected as the product mainly focuses its sale within the said area. The awareness of Hausboom sparkling juice product within the Klang Valley area is less than expected. As such, in order to increase Hausboom product awareness amongst the public residing in Klang Valley area, this research had been carried out. The objectives of this research is to determine the relationship between the different modes of promotion towards awareness of Hausboom sparkling juice product. The study uses primary data by conducting interviews and survey using self-administered questionnaire approach. The samples used in this study are 210 respondents who are the public residing in Klang Valley area. From the findings, it was found that there are a significant relationship between social media and print advertisement towards the increase of Hausboom sparkling juice product awareness. Finally, several marketing strategies were recommended for The Boom Beverage Sdn Bhd in order to expand its growth and increase awareness of Hausboom sparkiling juice product in the future